Implementation of GPS as a Validation System for Computer Laboratory Practicum Attendance - Prasetya, Anang Nur; Supriyanto, Supriyanto (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
The attendance system is a data management system for tracking individual or institutional attendance automatically, catering to personal or organizational management needs. Its primary objective is to serve as evidence of participation in activities, particularly in educational settings, where it validates attendance during the teaching and learning process, making attendance crucial. Manual attendance-taking in the Informatics Engineering Practicum at Ahmad Dahlan University is prone to difficulties in calculation, as well as risks of torn, wet, or lost attendance sheets, leading to prolonged processing times. The development of the Reglab application aims to enhance efficiency by securely managing attendance data, replacing manual processes. Additionally, it will integrate GPS technology to validate that practical activities occur within the laboratory. The Agile methodology guides the development of Reglab, leveraging existing systems while ensuring that resources are allocated effectively to accommodate the increasing volume of student and practicum schedule data. Student data will only be utilized for practicum registration, scheduling, and attendance purposes. The Agile approach ensures that the product output meets usability and user experience standards. System evaluation involves Blackbox testing and addressing user complaints received by the laboratory, with results aligning with expectations and a reduction in reported issues.